Dampak Kurangnya Transparansi Pengelolaan Keuangan Daerah Terhadap Pembangunan Lokal dan Kesejahteraan Masyarakat - Dandy Geofani Silaban; Winda Arisandi Situmorang; Rizky Khairani Br. Ginting; Fany Maysarah Sitohang; Nur Wida Yani; Sri Hadiningrum (Jurnal Relasi Publik, 2024)
This research aims to determine the impact of lack of transparency in regional financial management on local development and community welfare and accountability will remain a topic of concern in society. The public does not want acts of corruption to occur in government, because acts of corruption will not only be detrimental to state finances, they will also have an impact on hampering state development and reducing the level of social welfare. This type of research is a literature study. Library study activities related to methods of collecting library data, reading and taking notes and processing research materials. The results of the research inform that the phenomenon of non-transparency in the areas of budgeting, personnel, procurement of goods and services is certainly a fact that must be revealed based on the facts that can be observed and witnessed in various implementation of the main duties and functions of government employees. The cause of non-transparency in the various fields mentioned above is because there are factors that hinder the realization of transparency in the implementation of clean, authoritative and responsible regional government. Keywords: Transparency, Finance, Society